Poetry Translation Didactics in the EHEA - Belotto, Jesús (Estudios de Traducción, 2013)
This paper aims to offer an overview of the situation of poetry translation didactics where strengths can be highlighted, together with the challenges still to be met in this particular field of study. First of all, I will try to elaborate a critical analysis of methodologies and teaching resources, aiming to set the foundations for the development of specific teaching proposals for Poetry Translation in the context of the European Higher Education Area and reflecting on the potentialities and limitations of such proposals and on the interest to be raised in other areas of the translation professional market by the competencies acquired by students in these courses.
Keywords: didactics; translation; literature; poetry